Optimization of polarization control schemes for QKD systems - Muga, Nelson J.
In this work we develop an analysis of polarization control schemes suitable for quantum key distribution systems. Both time division multiplexing and wavelength division multiplexing based schemes are considered. A model for the optimization of the temporal separation between reference pulses and polarization encoded photons is presented. The model accounts for the reference pulse shape, the single photon detector gate width, and the respective temporal separation between them. The theoretical results are validated through experimental measurements. These results can be used to optimize the performance of polarization control schemes and therefore to optimize the polarization encoded quantum key distribution systems.